Continuous measurement of K and S release by means of ETV-ICP OES for high-temperature coal conversion processes. (15th May 2022) - Hommel, Caroline; Laabs, Marcel; Vogt, Thomas; Vogt, Carla; Guhl, Stefan; Meyer, Bernd
Highlights: Application of a new method for analyzing element release behavior from feedstock. Modification of ETV-ICP OES for analysis in atmospheres containing O2 . Interpretation of K and S release with different heating rates and gas compositions. Validation of measured element release by analyzing the residue and mass balance. Abstract: To estimate the fouling, slagging and corrosion potential of an energy feedstock during thermal carbon conversion processes, it is necessary to determine the temperature-dependent release behavior of relevant elements such as potassium and sulfur. For this purpose, this study employed electrothermal evaporation with inductively coupled plasma and optical emission spectroscopy (ETV-ICP OES) to investigate the element release in atmospheres containing oxygen both qualitatively and quantitatively. Using three different coal samples, it is shown that different heating rates (5–350 K/s) and gas atmospheres (0–10 vol-% O2 in the Ar gas stream) lead to differences in the release behavior. More sulfur is released when the oxygen content increases, whatever the sample. The release of potassium, on the other hand, depends on the sample matrix and the secondary reactions that occur. In two of the samples investigated, K is bound to silicates. These samples tend to form slags in which the potassium can bind. In the third sample, the potassium is organically bound or is bound to exchange sites on clay minerals and is released almost completely during the analyses.